TOPICAL ISSUES OF THE STATUS OF AN EXPERT AS A PERSON ASSISTING IN THE PRODUCTION - Chakhoyan, Artur (State and Law, 2025)
The article examined the provisions of the current legislation of the Republic of Armenia concerning the status of an expert, taking into account also that on June 30, 2021, the new Criminal Procedure Code of the Republic of Armenia was adopted, and from July 1, 2022, the new Criminal Procedure Code of the Republic of Armenia began to operate, which established completely new approaches and provisions concerning the procedural status of an expert, procedural actions performed by him on behalf of the body carrying out the production, the rights and obligations of the latter. In the light of the decision of the Plenum of the Supreme Court of the Republic of Armenia, the legal positions of the Court of Cassation of the Republic of Armenia and the provisions of the current Criminal Procedure Code of the Republic of Armenia, the status of the expert, the main objectives of the activities carried out by the expert were briefly presented, and some issues arising from this were discussed. In addition, given that currently there are no certain uniform criteria, restrictions or requirements established by the current legislation of the Republic of Armenia for an expert, the article discussed the adoption of a legal act regulating expert activity, the creation of a permanent independent qualification commission, which, in the author’s opinion, are relevant, since the presence or absence of a crime is often depends on the expert’s opinion. The importance of the adoption of the law on forensic expertise was emphasized, which in Armenia will unify all issues related to the expert sphere and the legal status of an expert, as well as define the social guarantees of an expert.